(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A significant turning point in the history of retail was the emergence of private-label brands. These brands are now more prevalent in the market across all product categories thanks to the retail sector’s explosive rise. With increasing market share and sales figures over the past two decades, they have greatly increased in popularity. They are currently giving the national brands a serious fight in terms of pricing, quality, distribution, promotion, packaging, etc. In other words, they have changed from being cheap, low-quality commodities to being expensive, high-quality things. On the other hand, according to various research reports, the majority of consumers still have unfavourable opinions of these companies and do not perceive them favourably in the marketplace, unlike national brands. The goal of this exploratory study was to examine a number of results established by past studies on private-label brands, including those related to the market success drivers, consumer perceptions, branding and positioning tactics, etc. In addition, this research has attempted to identify reasons why these companies are unpopular with consumers and why they lag behind the national brands in the market.